Solubilização do fosfato de rocha por Aspergillus niger - Alves, Glaicon Florisbelo (2012)
Phosphorus (P) is an essential macro element for maintenance of life of animals and plants. It is found in nature in the form of numerous minerals, such as apatite. The mining industry performs the extraction and processing of phosphate reserves. In the industrial process of this element considerable losses occur through industrial waste or through leaching by rain. The phosphorus dragged by rain can cause the reduction of oxigen of water bodies (eutrophication), necessary for maintaining life. Another industrial aspect concerns the production of fertilizers which traditionally utilize strong inorganic acids (sulfuric acid) for the obtaining of more soluble forms of phosphate, generating impactful byproducts to the environment. Within this context, this work proposed a possible alternative for the treatment of waste and for the traditional chemical processing, sulfuric route, by the use of Aspergillus niger, which excretes organic acid (less impactful) that by chelation mechanisms and ion exchange reactions, markedly increase the concentration of phosphorus in solution. Initially the fungus A. niger was found from soybean seeds removed from the field. 12 isolated fungi were obtained and designated numerically from 1 to 12 respectively, which were submitted to quantitative classification. In this step the two isolated fungi with the highest power of solubilization in a liquid form were selected, which are Isolated 7 (440 mg/L) and Isolated 9 (460mg/L), using the statistical methods Anova, Tukey and Scott-Knott in the quantitative classification. These solubilizattion values corresponded to ± 12% of P2O5 solubilization of phosphate rock. The next step was the experimental planning, more specifically, a Central Compound Rotational Delineation (CCRD). The relevant variables evaluated were the temperature in °C, substrate (glucose) in g/L and phosphate rock in g/L. As results were obtained for the two isolated fungi selected, the equations of the static models and graphics which represent the response surfaces between the variables. The Isolated 7 showed welldefined optimal points that were confirmed in the validation of the model, namely, 37°C for temperature, 41 g/L for the substrate and 36 g/L for the phosphate rock. The Isolated 9 didn´t show optimal points, but it showed an optimal region,namely, and 25 to 31 ° C for temperature, 28 to 37 g/L for the substrate and indifferent to phosphate rock, since this last is not shown to be significant in the experimental range. Even at this stage, it was verified the percentage of solubilization, ranging from 8 to 62% of P2O5 of the rock. After the planning it was measured the variation in the initial concentration of spores in the trials at concentrations of 105, 106, 107 and 108 spores per mL, and there was no statistical significance in the results at the end of the experiment for both fungi. It was also performed kinetic solubilization of the phosphorus, namely, to Isolated 7, the settling time has occurred within ± 36 days (5 weeks) after the start of the tests, reaching the value of 632 mg/L of P in solution. The solubilization rate was increased in the first 11 days. The settling time for the Isolated 9 occurred in ± 45 days (6 weeks), attaining the value of P in solution of 436 mg/L. The solubilization rate was increasing in the first 7 days. Finally, it was proposed a 6 L discontinuous bioreactor with aeration and recycle, which operated within optimum conditions defined above. It was obtained at the final test the value of 123 mg/L of soluble Phosphorus.